Some exact solutions of generalized Zakharov system - Demiray, Seyma Tuluce; Bulut, Hasan (Taylor & Francis Ltd, 2015)
In this paper, we seek exact solutions of generalized Zakharov system. We use extended trial equation method to obtain exact solutions of this system. Consequently, we obtain some exact solutions including soliton solutions, rational, Jacobi elliptic and hyperbolic function solutions of this system by using extended trial equation method.
Keywords: Trial Equation Method; Nonlinear Evolution-Equations; Fibonacci Function Solutions; Exp-Function Method; Optical Solitons; Wave Solutions; Conservation-Laws; Terms